Effect of Applying Ointment to Diabetic Ulcer before Modern Dressing : A Case Study - Siti Maghfirah Juniar N Djafar; Wa Ode Sri Asnaniar; Haeril Amir; Nur Wahyuni Munir (An Idea Nursing Journal, 2026)
Background: Diabetic ulcer is a chronic complication of diabetes mellitus,characterized by open wounds on the feet due to neuropathy, angiopathy, and decreased immunity, which impair healing and increase the risk of infection and amputation. Objective: This case study aims to describe the nursing care process and evaluate the effectiveness of ointment as a modern dressing in the healing of grade 1 diabetic ulcers. Methods: The study employed a case study approach using the nursing process (assessment, diagnosis, intervention, implementation, evaluation). The subject was a patient with a grade 1 diabetic ulcer at Clinic in Makassar City from August 6 to 11, 2025. Data were collected through interviews, direct observation, physical examination, and medical record review. The main intervention was wound care using epithelial ointment, patient education, blood glucose control, and wound monitoring. Evaluation was performed at each visit by assessing wound size, granulation, epithelialization, necrosis, exudate, and signs of infection. Results: On August 6, 2025, the wound measured 2.0 × 1.8 cm, with approximately 50% granulation, 20% epithelialization, 10% necrosis, and mild exudate. After care until August 11, 2025, granulation increased to ±70%, epithelialization to ±30%, necrosis decreased to <5%, exudate was minimal, and no signs of infection were observed. Conclusion: The patient also reported reduced pain and increased comfort during care.